Antusiasme Siswa terhadap Bahasa Arab Melalui Metode Bernyanyi Di Ekstrakurikuler SDI Hasanka - Muhammad Yasya; Aulia Mustika Ilmiani; Marliana Sya’diah (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
This community service initiative was designed to increase students' enthusiasm for Arabic language instruction by applying singing techniques in co-curricular activities at Hasanka Islamic Elementary School. The program emerged in response to the low interest of students in learning Arabic, which was considered to be lacking in variety and uninteresting for elementary school children. The approach applied is Participatory Action Research (PAR), which emphasizes active participation between educators, students, and facilitators in all stages of the activity. This method is implemented through a repetitive cycle that includes planning, implementation, observation, and joint evaluation to ensure that each activity is appropriate to the needs of the students and the school environment. Data was obtained through field observations, in-depth dialogues with teachers and students, activity records, and post-instruction group discussions. Descriptive analysis was conducted to identify changes in learning behavior, engagement levels, and students' emotional responses to singing activities. The findings showed a significant increase in student motivation and participation in Arabic language learning. The findings show a significant increase in student motivation and participation in Arabic language learning. Themed songs help them remember vocabulary more effectively, improve simple communication skills, and create a more enjoyable learning atmosphere. Furthermore, students have taken the initiative to compose lyrics and lead study groups. Implicitly, the application of singing techniques has proven to be effective not only in improving linguistic competence, but also in building confidence, creativity, and cooperation in the elementary school environment.